1978
DOI: 10.1530/acta.0.0870320
|View full text |Cite
|
Sign up to set email alerts
|

Iodoamino Acid Composition of Poorly Iodinated Human Thyroglobulin Fractionated by Isopycnic Centrifugation

Abstract: The distribution of iodotyrosines and iodothyronines has been studied in poorly iodinated 19 S thyroglobulins isolated by sucrose gradient centrifugation from five human thyroid tissue. The 19 S thyroglobulins have been fractionated by isopycnic centrifugation in 34.5 % rubidium chloride gradient. The distribution of iodoamino acids depends on the total iodine content of each fraction. The variations in MIT1) and DIT residues with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Direct analytical methods applied to Tg preparations from several species have shown that, in general, the first tyrosine residues to be iodinated are also the first to couple into iodothyronines (Lamas et al, 1974;Deme et al, 1976;Gavaret et al, 1977;Vignal et al, 1978) and that the different thyroxyls in Tg are synthesized in an order that is controlled by the tertiary structure of the protein (Rolland et al, 1972;Lamas et al, 1974;Deme et al, 1976;Gavaret et al, 1977;Maurizis et al, 1981). It is implicit in these observations that the iodothyronine-synthesizing sites in Tg differ in some way.…”
Section: Discussionmentioning
confidence: 99%
“…Direct analytical methods applied to Tg preparations from several species have shown that, in general, the first tyrosine residues to be iodinated are also the first to couple into iodothyronines (Lamas et al, 1974;Deme et al, 1976;Gavaret et al, 1977;Vignal et al, 1978) and that the different thyroxyls in Tg are synthesized in an order that is controlled by the tertiary structure of the protein (Rolland et al, 1972;Lamas et al, 1974;Deme et al, 1976;Gavaret et al, 1977;Maurizis et al, 1981). It is implicit in these observations that the iodothyronine-synthesizing sites in Tg differ in some way.…”
Section: Discussionmentioning
confidence: 99%